Monitoring Smart Applications for Monitoring and Controlling of IoT-Based Strawberry Hydroponic Plants - Willi Bianyosa Arif Wibiya; Aris Nasuha (Journal of Robotics, Automation, and Electronics Engineering, 2023)
Hydroponic farming has become an attractive option in strawberry cultivation as it provides better control over the growing environment of the plants. However, proper management and continuous monitoring are challenges often faced by farmers in hydroponic farming practices. Therefore, in this study, we designed an IoT-based application that aims to monitor and control strawberry hydroponic farming through smartphone devices. The method used in this research involves developing an application that connects with various sensors installed in the hydroponic farm environment. The data obtained from the sensors is transmitted in realtime through the IoT network. In addition to the monitoring function, the application is also equipped with a control system that can be customized according to the needs of farmers. The result of this research is an application that can work from a short distance (local) or a long distance (cloud). The application is equipped with a hazard alarm notification system. The feature allows farmers to take action to maintain the health and quality of strawberry plants. The use of this application is expected to help make it easier for farmers to monitor and control hydroponic farming to be more efficient and optimize crop yields.